Design and application of the field test TIVRE‐Basket for the evaluation of the aerobic resistance in basketball players - A. Vaquera; J. C. Morante; J. García-López; J. A. Rodríguez-Marroyo; C. Ávila; P.R. Mendonca; J.G. Villa (Asociación Española de Ciencias del Deporte, 2010)
Considering basketball as an acyclic and discontinuous sport it has been designed and validated a field test (TIVRE-Basket) for the evaluation of the specific resistance of the basketball player who allows to identify the anaerobic threshold and to analyze his capacity of recovery. 18 professional basketball players realized a treadmill test (PowerJog M30), with measurement of VO2máx and determination of the anaerobic ventilatory threshold (VT2). 48 h later realized the field test TIVRE-Basket with heart rate monitors (Polar Vantage NV). There were neither significant differences between the treadmill test and the TIVRE-Basket neither in the maximum HR (189.2±1.3 vs 189.6±1bpm) nor the HR-anaerobic threshold (175.2±8 vs 176.5±7bpm), but if in the maximum speed (17.58±0.1 vs 14.2±1.2 km/h) and in the anaerobic threshold speed (12.9±0.4 vs 10.34±0.1 km/h). Nevertheless there were obtained significant interrelations (p <0.01) between the VO2max and the maximum speeds in the treadmill and TIVRE-Basket. Also significant differences were only below the intervallic anaerobic threshold in the cardiac maximum frequencies of every interval of effort and the minimum in every recovery. The TIVRE-Basket is useful and specific in the evaluation of the aerobic resistance and capacity of recovery of the basketball players. Key words: Basketball, Maximum Consumption of Oxygen, Anaerobic Threshold, Recovery, Field test